Feasibility assessment of magnetic sensors for measurement of Hall current induced changes to the static magnetic field nearby a Hall thruster - Morozko, Zoe, author; Williams, John, advisor; Stansloski, Mitchell, committee member; Thornton, Christopher, committee member (Colorado State University. Libraries, 2013)
A Hall thruster is an electric propulsion device that produces thrust electrostatically by accelerating propellant to velocities 5 to 10 times higher than is achievable using conventional chemical thrusters. This is accomplished through the application of static, crossed electric and magnetic fields that are concentrated in a region close to the exit plane of the thruster. During operation an azimuthal plasma-electron current develops in the region where the electric and magnetic fields are concentrated. This embedded plasma current is referred to as the Hall current. The thrust produced from accelerating the propellant is transferred to a satellite or spacecraft through interaction between the Hall current and the magnetic coils used to produce the static magnetic field within the thruster. The Hall current can be calculated and the thrust can be determined in real time by measuring the magnetic field produced by the Hall current using sensors located external to the thruster. This work investigates the feasibility of placing magnetic sensors in the regions close to the exit of the thruster to measure the external magnetic field and correlate it to the Hall current. A finite element magnetic solver was used to identify several locations outside of the thrust plume and near the pole piece where the magnetic field magnitude changes by several Gauss in a background field level of ~50 Gauss. Magnetic sensors based on the giant magnetoresistive effect were identified as acceptable with regard to sensitivity, and measurements made with these sensors in a simulated high background magnetic field environment demonstrated that changes of 0.5 Gauss could be easily measured. This work also presents the development of a thrust stand that will be useful in future work to demonstrate the overall concept. Special focus was directed to the design of the data acquisition system and in-vacuum calibration system used to make measurements with the thrust stand.
Keywords: electric propulsion; Hall thruster; magnetic field measurement; magnetic sensors; plasma propulsion; thrust stand